How the Media Places Responsibility for the COVID-19 Pandemic—An Australian Media Analysis - Thomas, Trevor; Wilson, Annabelle; Tonkin, Emma; Miller, Emma R.; Ward, Paul R. (Frontiers in Public Health, 2020)
Global pandemics are likely to increase in frequency and severity, and media communication of key messages represents an important mediator of behavior in response to public health countermeasures. Where the media places responsibility during a pandemic is therefore important to study as blame is commonly used as a tool to influence public behavior but can also lead to the subjective persecution of groups. The aim of this paper is to investigate where the media places responsibility for COVID-19 in Australia. Specifically, we identify the key themes and frames that are present and observe how they changed in relation to government actions and progression of the pandemic. Understanding media representations of the COVID-19 pandemic will provide insights into ways in which responsibility is framed in relation to health action. Newspaper articles from the Australian and the Sydney Morning Herald were sampled between January 20 and March 31 2020 on every second Monday. Factiva was used to identify and download newspaper articles using the following search criteria: “COVID-19" OR coronavirus OR "Wuhan virus" OR "corona virus" OR "Hebei virus" OR "wet market" OR (Wuhan AND virus) OR (market AND Wuhan and virus) or (China AND Virus) or (Novel AND Virus). Articles were imported into Nvivo and thematic and framing analyses were used. The results show that framing of the pandemic was largely based on societal issues with the theme of economic disruption prevalent throughout. Moral evaluations of the pandemic were infrequent initially but increased co-incident with the first signs of ‘flattening of the curve’. Explicit examples of blame were rare but commonly implied based on the causal origin of the virus. The Australian printed media were slow to report on the COVID-19 pandemic, in addition they were reluctant to apportion blame until after confirmed case rates had begun to slow. This is interpreted as being due to an evaluation of the pandemic risks as low by the media and therefore the tools of othering and blame were not used until after the study period when the actual risks had begun to abate, more consistent with an inquiry than a mediating mechanism.